PERAN AKAD KAFALAH DALAM PRODUK PEGADAIAN SYARIAH TERHADAP IMPLEMENTASI PENJAMINAN DAN MITIGASI RISIKO - Umi Kulsum, Siti; Pangestu, R. Ali; Abdul Aziz , Imam (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2024)
problematic financing (bad credit) for customers due to the death of customers and customers whose businesses go bankrupt, resulting in losses for the Sharia Pawnshop, Margonda Depok Branch, as the guarantor of the financing.This research aims to determine the implementation of the contract, determine the implementation of the kafalah contract at the Margonda Depok Branch Sharia Pawnshop and to determine the role of the kafalah contract in transaction guarantees, identify the risks that arise in the kafalah contract and the extent of its contribution in mitigating risks for customers and pawnshops.The type of research used in this thesis is descriptive qualitative research with a case study approach. The analytical tool used is the Miles and Huberman model. The results of this research show that 1) The implementation of the kafalah contract in Pegadaian Syariah products, Margonda Depok Branch is running in accordance with fatwa No.11/DSN-MUI/VI/2000 concerning kafalah and its application is in micro financing products. 2) The role of the kafalah contract in guaranteeing transactions on sharia pawnshop products is to provide guarantees for payment of customer debts in the event of default or inability to pay debts and help prevent both parties involved from losses and injustice, mitigating risks in products that use the kafalah contract from the pawnshop. customers to Pegadaian Syariah Margonda Branch, namely: (a) regular monitoring, (b) backing up data digitally, (c) early identification of customer data, (d) socialization, (e) making binding agreements